Investigation of the relationship between hamstring flexibility and hamstring and quadriceps muscle strengths in athletes - Akinoglu, B.; Kabak, B.; Ünüvar, E.; Kocahan, T. (Medicina dello Sport, 2020)
BACKGROUND: Hamstring injury is one of the most common muscle injuries in sports. This type of injury is known to be caused by excessive strain and low strength of the hamstring muscle. The purpose of this study was to examine the relationship between the flexibility of the hamstring muscle and, the concentric and eccentric muscle strength of both the hamstring and quadriceps muscles in athletes, including the comparison of these parameters based on genders. METHODS: This study a cross-sectional study, in which a total of 253 athletes (age: 17±2 years; body weight: 65.04±14.35 kg; height: 1.72±0.10 m; Body Mass Index: 21.73±3.23 kg/m²; sports year: 7.46±2.82 years; males: 170; females: 83) have participated. Hamstring muscle flexibility was determined by measuring the active knee extension (AKE) angle using a Goniometer. The strength of the hamstring and quadriceps muscles were evaluated using Isomed 2000® Isokinetic Dynamometer device based on concentric-concentric and eccentric-eccentric values at 60º/sec and 180º/sec, respectively. RESULTS: A weak negative correlation was found between the AKE angle and, hamstring and quadriceps concentric muscle strength at both angular velocities in female athletes (r=240/406; P<0.05), whereas there was no correlation in male athletes (P>0.05). On the other hand, there was no correlation between AKE angle and, hamstring and quadriceps eccentric muscle strength at both angular velocities in either female or male athletes (P>0.05). It has been determined that female athletes have higher AKE angle than male ones, whereas the concentric and eccentric strength of their hamstring and quadriceps muscles are weaker (P<0.05). CONCLUSIONS: Our study suggests that flexibility may affect the concentric muscle strength negatively in female athletes as they are more flexible and have lower muscle strength as compared to male athletes. Concentric and eccentric strength exercises should be included in the training programs of female athletes, and muscle flexibility enhancing exercises be included for male athletes.